53.1k views
5 votes
Complete the square for each expression. Write the resulting expression as a binomial. x^2+26x+____

User Kai Mechel
by
6.1k points

1 Answer

6 votes

Given the expression written in the following form:


ax^2+bx+c

You can complete the square for the expression by following these steps:

1. You must take the coefficient "b", divide it by 2 and then you must square it:


((b)/(2))^2

For this case you can identify that "b" is:


b=26

Therefore:


((b)/(2))^2=((26)/(2))^2=(13)^2=169

2. Complete the square by adding 169 to the expression given:


=x^2+26x+169

3. Factor it in order to express it as a binomial.

The answer is:


=(x+13)^2

User Sergey Romanovsky
by
5.8k points